Time‐Dependent Bias in Instantaneous Ceptometry Caused by Row Orientation. Issue 1 (1st December 2018) - Salter, William T.; Gilbert, Matthew E.; Buckley, Thomas N.
Abstract : Ceptometry (the measurement of average photosynthetically active radiation under a plant canopy using many individual light sensors connected in parallel on a long bar) is commonly used to infer canopy light interception as well as leaf area index. Typically, the user places a ceptometer below the canopy and records a measurement, which is compared with a concurrent above‐canopy measurement to produce a value of transmittance and then corrected for the effects of solar zenith and solar beam fraction. In row crops, canopy architecture is often systematically clumped in ways that may bias inferences based on ceptometer measurements. The role of spatial sampling in bias due to clumping has been extensively studied in the literature, but time‐dependent bias has not. We assessed this bias using 68 handmade continuously recording ceptometers in 239 wheat ( Triticum aestivum L.) genotypes in Australia and made confirmatory measurements in California. We found that canopy properties inferred from instantaneous ceptometry varied widely, both randomly and systematically in time, when compared with properties inferred from continuous measurements. However, these biases tended to be somewhat similar across genotypes on a given day, arising from the interaction of solar zenith and non‐random features of the canopy distribution caused by row planting. We recommend that continuous ceptometry be used in conjunction with instantaneous ceptometry to correct for these biases, and we provide schematics for low‐cost handmade ceptometers.